Double threat : Canadian Jews, the military, and World War II - Bessner, Ellin 1961- (New Jewish Press, University of Toronto Press, 2018)
"The role played by the Canadian Jewish Community during World War II, particularly the approximately 17,000 individuals who enlisted, representing 10% of the Jewish population in Canada at the time. Interviews with surviving veterans, and family of deceased veterans, about their experiences provide a detailed portrait of the experience. Profiles of military heroes are included. The experience of the Canadian Jews, both men and women, who served in virtually every campaign and every branch of the military is described. The role of the homeland community, community organizations including Jewish newspapers, and the clergy is also covered."...